Testing the effects of an empowerment‐based leadership development programme: part 1 – leader outcomes. (8th May 2013) - MacPhee, M.; Dahinten, V.S.; Hejazi, S.; Laschinger, H.; Kazanjian, A.; McCutcheon, A.; Skelton‐Green, J.; O'Brien‐Pallas, L.
<x xml:space="preserve">Abstract</x> Aim To determine if a leadership development programme based on an empowerment framework significantly increased leaders' use of empowering behaviours. Background Leadership programmes are effective ways to prepare nurse leaders for their complex roles. Relational competencies, such as leader empowering behaviours, are associated with improved leader, staff and practice environment outcomes. Methods A quasi‐experimental, pre‐test–post‐test design was used to compare perceptions and self‐reported behaviours of leaders who participated in a year‐long leadership programme with those of similar leaders who did not attend the programme. Multiple regression analyses were used to evaluate a conceptual framework of leader empowerment. Results The leadership programme was directly associated with leaders' perceptions of using more empowering behaviours. Leader empowering behaviours were also associated with feelings of being structurally empowered, mediated through feelings of being psychologically empowered, although the source of empowerment needs further investigation. Conclusions Leaders' use of empowering behaviours can be increased through focused training and through a workplace empowerment process. Implications for nurse management Leader empowering behaviours have been shown to be associated with more engaged staff and healthier work environments. Based on study results, we suggest that these behaviours are teachable, and they should be emphasized in leadership development programmes.